Speech Patterns and the Concept of Utility in Cognitive Maps: The Case of Integrative Bargaining - Simons, Tony (Academy of Management Journal, 1993)
This study's premise is that negotiation dyads' conceptualization of utility is a key component of their ?cognitive maps,? or internal representations, that influences the dyads' assumptions and motivation. A linguistic indicator was developed for utility as an objective attribute, utility as a subjective preference, and utility as an interpersonal relationship. An analysis of 79 transcripts from two negotiation studies revealed that dyads whose members conceptualized utility as a subjective preference reached more integrative agreements than dyads displaying either of the other two conceptualizations. Also, as hypothesized, linguistic patterns from the first half of negotiation were better predictors of agreements than linguistic patterns from the second half of negotiation.